Risk Factors for Delirium Are Different in the Very Old: A Comparative One-Year Prospective Cohort Study of 5,831 Patients - Marquetand, Justus; Bode, Leonie; Fuchs, Simon; Hildenbrand, Florian; Ernst, Jutta; von Känel, Roland; Boettger, Soenke (Frontiers in Psychiatry, 2021)
Background: In an ever-ageing society, health care systems will be confronted with an increasing number of patients over 80 years (“the very old”). Currently, knowledge about and recommendations for delirium management are often based on studies in patients aged 60 to 65 years. It is not clear whether these findings apply to patients ≥80 years. Aim: Comparison of younger and older patients with delirium, especially regarding risk factors. Methods: In this prospective cohort study, within one-year, 5,831 patients (18-80 years: n = 4730; ≥80: n = 1101) with delirium were enrolled. The diagnosis of delirium was based on the Delirium Observation screening scale (DOS), Intensive Care Delirium Screening Checklist (ICDSC) and a DSM (Diagnostic and Statistical Manual)-5 construct of nursing instrument. Sociodemographic trajectories, as well as the relevant predisposing and precipitating factors for delirium, were assessed via a multiple regression analysis. Results: The very old were more commonly admitted as emergencies (OR 1.42), had a greater mortality risk (OR 1.56) and displayed fewer precipitating risk factors for the development of a delirium, although the number of diagnoses were not different (p=0.325). Predisposing factors were sufficient almost alone for the development of delirium in patients ≥ 80 years of age; in 18-80 years of age, additional precipitating factors had to occur to make a delirium possible. Conclusion: When relevant predisposing factors for delirium are apparent, patients over 80 years of age require comparatively few or no precipitating factors to develop delirium. This finding should be taken into account at hospitalization and may allow better treatment of delirium in the future.